Hybrid Recursive Active Filters for Duplexing in RF Transmitter Front-Ends - Gottardo, Giuseppe; Donati, Giovanni; Musolff, Christian; Fischer, Georg; Felgentreff, Tilman (Radio Science, 2016)
Duplex filters in modern base transceiver stations (BTS) provides the channel shape in order to perform common frequency division duplex (FDD) operation. Usually they are designed as cavity filters, which are expensive and have big dimensions. Thanks to the emerging digital technology and fast digital converters, it is possible to transfer the efforts of designing analog duplex filters into digital numeric algorithms applied to feedback structures, operating on power amplifiers in transmitters. This solution provides the shaping of the signal spectrum directly at the output of the radio frequency (RF) power amplifiers (PAs) relaxing the transmitter design especially in the duplexer and the antenna sections. The design of a digital baseband feedback applied to the analog power RF amplifiers (hybrid filter) is presented and verified by measurements. A model to describe the hybrid system is investigated and the relation between phase and resonance peaks in the resulting periodic band-pass transfer function is described. The stability condition of the system is analyzed using Nyquist criterion and defining a safe work region in order to avoid oscillation. A solution involving a number of digital feedback and forward branches is investigated defining recursive structure parameters of the hybrid filter. This last solution allows the closed loop system to show at the output of the RF amplifier a periodic band-pass with up to 500 KHz bandwidth. Moreover, the band-pass magnitude reaches up to 17 dB difference between maximum gain and attenuation.
elib2cris::1512001600,gottardo2016
Keywords: active filter; feedback amplifier; base station; stability analysis; interference suppression; band-pass filters